Pediatric Tuina for promoting growth and development of preterm infants: A protocol for the systematic review of randomized controlled trail. Issue 18 (May 2018) - Zhang, Xinghe; Guo, Taipin; Zhu, Bowen; Gao, Qing; Wang, Hourong; Tai, Xiantao; Jing, Fujie
Abstract: Background: Preterm infants are babies born alive before 37 weeks. Many survived infants concomitant with defects of growth and development, a lifetime of disability usually as following when insufficient intervention. In early intervention of preterm infants, pediatric Tuina shows good effect in many Chinese and some English clinical trials. This systematic review is aimed to evaluate the efficacy and safety of pediatric Tuina for promoting growth and development of preterm infants. Methods: The electronic databases of Cochrane Library, MEDLINE, EBASE, Web of Science, Springer, World Health Organization International Clinical Trials Registry Platform, China National Knowledge Infrastructure, Chinese Biomedical Literature Database, Wan-fang database, Chinese Scientific Journal Database, and other databases will be searched from establishment to April 1, 2018. All published randomized controlled trials (RCTs) about this topic will be included. Two independent researchers will operate article retrieval, screening, quality evaluation, and data analyses by Review Manager (V.5.3.5). Meta-analyses, subgroup analysis, and/or descriptive analysis will be performed based on included data conditions. Results: High-quality synthesis and/or descriptive analysis of current evidence will be provided from weight increase, motor development, neuropsychological development, length of stay, days of weight recovery to birthweight, days on supplemental oxygen, daily sleep duration, and side effects. Conclusion: This study will provide the evidence of whether pediatric Tuina is an effective early intervention for preterm infants. Ethics and dissemination: There is no requirement of ethical approval and informed consent, and it will be in print or published by electronic copies. Trail registration number: This systematic review protocol has been registered in the PROSPERO network (No. CRD42018090563).